Biological Activity of trans-2-Hexenal Against Bradysia odoriphaga (Diptera: Sciaridae) at Different Developmental Stages. Issue 1 (11th July 2015) - Chen, Chengyu; Mu, Wei; Zhao, Yunhe; Li, Hui; Zhang, Peng; Wang, Qiuhong; Liu, Feng
Abstract : trans -2-Hexenal, one of the C6 green leaf volatiles, is potentially useful for the control of Bradysia odoriphaga Yang et Zhang. In this study, the biological activity of trans -2-hexenal on B. odoriphaga was assessed in the laboratory. trans -2-Hexenal was observed to kill B. odoriphaga in different developmental stages at a relatively low concentration under fumigation. The respiration rate in the male treatment group decreased from 131.44 to 4.07 nmol/g·min with a prolonged fumigation time, while the respiration rate in females decreased from 128.82 to 24.20 nmol/g·min. Male adults exhibited a more sensitive electroantennogram response at 0.05–500 μl/ml at the dose of 10.0 μl than female adults. Moreover, trans -2-hexenal had a repellent effect on adults based on the results with a Y-tube olfactometer at 10.0 μl, as shown by the deterrent rate of male and female adults with 96.67% and 98.33%, respectively. The results showed that trans -2-hexenal had good biological activity in different developmental stages of B. odoriphaga, which could reduce the need for, and risks associated with, the use of traditional insecticides and enable nonharmful management.